The Non Performed Financing Effect on Financing and Control Strategy and Handling of Sharia Commercial Banks - Sofyan Halim; Mohamad Torik Langlang Buana (Universitas Mercu Buana, 2021)
Problematic financing or often referred to as Non-Performed Financing is financing that has difficulty paying off, either due to lack of accuracy in the analysis of lending or due to economic conditions that experience instability which results in failure in most economic activities. The research conducted is examining the problematic financing whether it influences the decision-making of financing with various Islamic contracts, namely the mudharabah, musyarakah, Murabaha, salam, istishna, Ijarah, Qard, and Hiwalah agreements and examines the strategies carried out by the Shari'ah Commercial Bank to do handling the problematic financing.The study was conducted with quantitative and descriptive methods, with the results of the study that NPF In Mudharabah, Murabahah, and ijarah contract financing there is a positive relationship between the two variables, so it can be concluded that the increase in NPF does not affect the fund distribution policy with mudharabah agreements, because The contract positively increases, while the NPF for financing with Musyarakah, Istishna and qardh contracts has a negative relationship so it can be concluded that the NPF in financing with the Musharaka contract has a negative effect in the sense that the Shari'ah Commercial Bank in general distributing financing to customers is limited due NPF by paying attention to redline facilities, BUS only provides financing facilities for businesses that contain minimal risks. NPF in general, Sharia Commercial Banks do not really influence policies in financing distribution to customers with various financing agreements. The results of the regression determination analysis show that the percentage effect of NPF on financing distribution policies with mudharabah, musyarakah, Murabaha, Murabaha, istishna, ijarah, and qardh contracts in Islamic Commercial Banks is 33.8%, while the remaining 66.2% is influenced by variables others not formulated in this research model. The Normality Test results show that the NPF and Musyarakah contract financing is normally distributed while the Mudharabah, Murabahah, Istishna, Ijarah and Qardh variables are not normally distributed because the significance is lacking.The Sharia Commercial Bank in dealing with Non-Performed Financing issues generally refers to the MUI Sharia Board Fatwa, Bank Indonesia Regulations, and OJK Regulations, which are with rescheduling, reconditioning, restructuring and Write Off. This research is expected to be useful for stakeholders related to this research and for future researchers to be able to improve further research.